2019
DOI: 10.1002/ajp.22963
|View full text |Cite
|
Sign up to set email alerts
|

Detection of insect prey by wild common marmosets: The effect of color vision

Abstract: Most species of New World primates have an unusual color vision pattern that can affect an individual's ability to detect food. Whereas males can only be dichromatic, females can be either dichromatic or trichromatic. Trichromats are expected to have an advantage in detecting conspicuous food whereas dichromats should be better at locating cryptic resources. Here we aimed to understand how color vision phenotype influences insect foraging by five groups of common marmosets living in a semiarid environment. We … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 46 publications
0
8
0
Order By: Relevance
“…During the data collection time, the mean temperatures ranged from 18.5°C to 35.7°C according to the Brazilian National Institute for Meteorology (INMET), Cabaceiras station. Most marmosets of the area were well habituated to the presence of humans from previous studies (e.g., Abreu et al, 2016, 2019; Caselli et al, 2018; De la Fuente et al 2014, 2019). In particular, three groups (Casa, Coqueiro, and Vacas) were already habituated to humans, whereas two groups (Star Wars and Azul) were newly habituated for this study.…”
Section: Methodsmentioning
confidence: 69%
“…During the data collection time, the mean temperatures ranged from 18.5°C to 35.7°C according to the Brazilian National Institute for Meteorology (INMET), Cabaceiras station. Most marmosets of the area were well habituated to the presence of humans from previous studies (e.g., Abreu et al, 2016, 2019; Caselli et al, 2018; De la Fuente et al 2014, 2019). In particular, three groups (Casa, Coqueiro, and Vacas) were already habituated to humans, whereas two groups (Star Wars and Azul) were newly habituated for this study.…”
Section: Methodsmentioning
confidence: 69%
“…There is currently little evidence that different dichromatic phenotypes vary in detecting different types of insects or fruits (e.g., Abreu et al, 2019), and further study will be important for understanding the ecology and evolution of opsin genotypes.…”
Section: Visual Ecology Of Plecturocebus Pithecia and Saimirimentioning
confidence: 99%
“…Investigations presenting camouflaged geometric figures to humans (Morgan et al 1992;Saito et al 2006) and non-human primates (Saito et al 2005) showed that dichromats, when compared with trichromats, were more capable of breaking camouflage and detected hidden shapes. Indeed, some naturalistic/ecological studies gave support to the idea that the visual polymorphism of Neotropical primates balances (Hiwatashi et al 2010) the advantages of dichromats in recognizing hidden objects in the environment (Caine et al 2003;Melin et al 2007;Smith et al 2012) and those of trichromats in detecting conspicuous targets (Caine and Mundy 2000;Smith et al 2003;Melin et al 2013Melin et al , 2017Pessoa et al 2014;Abreu et al 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 12, 2021. ; https://doi.org/10.1101/2021.04.11.439391 doi: bioRxiv preprint 6 molecular approaches (Travis et al 1988;Tovée et al 1992;Hunt et al 1993;Wilder et al 1996;Shyue et al 1998;Kawamura et al 2001;Surridge and Mundy 2002;Pessoa et al 2005a;Freitag and Pessoa 2012;Pessoa et al 2014;Moreira et al 2015;Abreu et al 2019;Pessoa and Freitag 2019;Mantovani et al 2020), showing that C. jacchus expresses a tri-allelic visual polymorphism, that encodes M/L pigments with maximum absorption at 543 nm, 556 nm and 562 nm, and allows the existence of six visual phenotypes (three dichromats and three trichromats) in natural populations (Jacobs 2007).…”
Section: Introductionmentioning
confidence: 99%